The Pluralist Theory of Ethics Programs Orientations and Ideologies: An Empirical Study Anchored in Requisite Variety - Martineau, Joé T.; Johnson, Kevin J.; Fauchant, Thierry C. (Journal of business ethics)
We propose, in this article, a pluralistic theory of ethics programs orientations, empirically derived from the statistical analysis of responses to an ad hoc questionnaire on organizational ethics practices. The results of our research identify six different orientations to ethics programs, corresponding to as many types of organizational ethics practices. This model goes beyond the traditional opposition between a compliance orientation, focused on the regulation of behavior and the detection of deviance, and a values-based orientation, which is said to be more reflective and enabling, and allows for a more sophisticated understanding of the composition of ethics programs. Drawing from the theory of requisite variety, we suggest that these six orientations are not to be considered in opposition but rather as complementary and even synergistic. In doing so, this pluralism has the potential to counter the potential deleterious effects of dominant logics and ideologies in organizations. Our model thus allows for a more empirical analysis of organizational ethics practices and programs and provides a new analytical framework for research and practice in considering the principle of requisite variety in ethics management. This represents, in our opinion, a contribution to the advancement of knowledge and practice in organizational ethics.